Trends and geospatial distribution of stillbirths in Uganda, 2014-2020 - Petranilla Nakamya; Allan Komakech; Stella M. Migamba; Claire Biribawa; Benon Kwesiga; Lilian Bulage; Alex R. Ario; Felix Ocom (BMC, 2024)
Abstract Introduction Uganda with 17.8 stillbirths per 1,000 deliveries in 2021, is among the countries with a high burden of stillbirths globally. In 2014, Uganda adopted the World Health Organization Every New-born Action Plan (ENAP), which targets < 10 stillbirths per 1,000 deliveries by 2035. Little is known about the trends of stillbirth burden since ENAP was introduced. We assessed the temporal, and spatial distribution of stillbirths, in Uganda, 2014-2020, to inform programming for safe pregnancies and deliveries. Methods We obtained and analysed stillbirth surveillance data from the District Health Information System, 2014-2020. A stillbirth was defined as the death of a foetus > 28 weeks of pregnancy or weighing > 1000 g before or during birth and reported to a health facility. We calculated annual incidence rates of stillbirths per 1,000 deliveries at district, regional, and national levels. We used logistic regression to determine the significance of trends. Results The overall national annual incidence of stillbirths decreased from 24/1,000 deliveries in 2014 to 17/1,000 deliveries in 2020. During the same period, reporting rates declined from 71% in 2014 to 46% in 2020. The central region continuously had the highest incidence rate for the past 5 years despite the largest decline (OR = 0.79; CI = 0.77-0.83, P < 0.001) while the eastern region had the smallest decline (OR = 0.59; CI = 0.57-0.61, P < 0.001). Districts with persistently high annual incidence rates of stillbirths (> 30/1000) included Mubende, Kalangala, Hoima, and Nebbi. There was no difference in the reporting rates of the most- vs. least-affected districts. Conclusion Even with suboptimal reporting, the incidence of stillbirths remained above the national target. Specific areas in the country appear to have particularly high stillbirth rates. We recommend continuous capacity building in managing pregnant women with an emphasis on the most affected districts, and investigation into the reasons for low reporting.